Digital Village Governance Programme Gisik Cemandi Sidoarjo East Java through Digital Visual Branding - Kristiyono, Jokhanan; Prasetyo, Dwi; Rahmawati, Aulia Afniar; Kristama, Baswara Yua (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: Gisik Cemandi Village, Sedati District, Sidoarjo Regency, aims to enhance its digital visual branding as a key part of its digital communication strategy. The program focuses on creating a digital strategic plan, which includes goals, strategies, policies, and investment priorities for both short and long term. Additionally, training and developing human resources is crucial for effective use of digital governance, alongside proper management and supervision of digital communication technology.Method: From August to September 2023, the activities included Digital Visual Branding counseling, Creative Content Production training, and CMS mentoring for the village’s official website, enabling efficient information dissemination.Practical Applications: The program produced three key outcomes: Digital Visual Branding Training to help the village community develop their brand identity in the digital world; Creative Content Creator Training to improve content creation for digital marketing, and; the creation of a website for the village's Digital Information Governance.Conclusion: In conclusion and advice, through this program, the community was provided with the visual design skills and branding understanding needed to strengthen the village's brand image online. The training focuses on creative content development that assists the village's digital marketing and branding efforts. This provides the ability to create engaging and informative content to increase the village's visibility online.